EFEKTIFITAS REFLEK PUTING MAMMAE (RPM) PADA IBU BERSALIN KALA IV DENGAN PERDARAHAN POSTPARTUM DI KLINIK PRATAMA JAMBU MAWAR PEKANBARU TAHUN 2018 - susi hartati (STIKes Mitra Husada Medan, 2018)
AbstractMaternal Mortality Rate in Riau Province in 2015 was 108.9 every 100,000 live births, currently the cause of maternal death is 55% of bleeding events in maternity mothers in Riau Province. The highest number of post partum at the Pratama Clinic of Jambu Mawar in Pekanbaru with a total of 159 postpartum every year. The purpose of this study was to determine the effectiveness of nipple reflexology (RPM) on maternity mothers in the fourth stage with postpartum hemorrhage at the Primary Clinic of Jambu Mawar Pekanbaru in 2018. This type of research was quantitative with a quasi-experimental design. The research was carried out at the Pratama Clinic Jambu Mawar Pekanbaru. Time from January to August 2018. Population of 87 people, a sample of 10 people every group. Analyze univariate and bivariate data using Chi Square test. The results of this study were a relationship between nipple stimulation in maternity at stage IV with post partum hemorrhage at the Pratama Clinic of Jambu Mawar Pekanbaru with p-value = 0.048 and there was a relationship between early breastfeeding initiation (IMD) in maternity at stage IV with post partum hemorrhage in Clinic Pratama Jambu Mawar Pekanbaru p-value = 0.033 α = 0.05. Suggestions are expected to the Pratama Clinic of Jambu Mawar Pekanbaru to do Mammae Nipple Reflexology (RPM) can be done on post partum mothers to reduce bleeding. Keyword : Early Breastfeeding Initiation, Mammae Nipple Reflexology and Hemoragghe Post Partum